A qualitative analysis of resilience related strengths and struggles of unaccompanied refugee minors in Norway - Alkiviadou, Maria (2017)
This research was carried out with the purpose of identifying how unaccompanied refugee minors (URMs) become stronger and can adapt in the current multiple domains of their life in Western Norway (e.g. school, community and social life), considering the added challenges of acculturation. The study explored risk and protective factors that influence URMs emotional well-being and coping, as well as the development of recovery of function or resilient adaptation patterns in the face of previous significant adversity. The qualitative microethnographic study took place with a group of four URMs and a group of two professionals from a public organization in a West Norwegian municipality. Data collection techniques included interviews with URMs and the professionals who are working with them, as well as participant observation and field notes. The data collection was focus on identifying URMs’ perceptions on their challenges, strengths and environmental resources that develop or hinder their resilience. The findings indicated challenges that limit resilience among refugee minors at the stage of resettlement in the western Norway, including lack of support and guidance, language barrier, cultural contrasts, cultural shock and acculturation stress. It was also found that participant’s personal attributes including spirituality and faith, self-efficacy, natural abilities, hard work, persistence and determination, gratitude, aspirations, motivations and focus on goals foster their resilience. Finally, it was possible to identify and address how factors related to environmental resources, culture and context aspects enhance or hinder resilience adaptation patterns. Perceived factors that promote participants’ resilience, including social support from professionals, peers and community resources and provision of opportunities for participation in social activities, positive affiliation with peers and professionals, support and knowledge received from the teachers, valuing education and healthy Norwegian refugee policy. The most important determinants perceived by the participants as those that hinder their resilience were the prevalence of risk factors such as stereotypes and stigma, cultural divides, and loss of their family. The findings from this inquiry provide new insights on the development of preventative interventions and programs or improving existing ones and determining policy design in social care to promote resilience and mental health recovery for unaccompanied refugee minors during the post-migratory stage.